Genetically Engineered Triple MAPT-Mutant Human-Induced Pluripotent Stem Cells (N279K, P301L, and E10+16 Mutations) Exhibit Impairments in Mitochondrial Bioenergetics and Dynamics. - Szabo, Leonora; Grimm, Amandine; García-León, Juan Antonio; Verfaillie, Catherine M.; Eckert, Anne (MDPI, 2023)
Pathological abnormalities in the tau protein give rise to a variety of neurodegenerative diseases, conjointly termed tauopathies. Several tau mutations have been identified in the tau-encoding gene MAPT, affecting either the physical properties of tau or resulting in altered tau splicing. At early disease stages, mitochondrial dysfunction was highlighted with mutant tau compromising almost every aspect of mitochondrial function. Additionally, mitochondria have emerged as fundamental regulators of stem cell function. Here, we show that compared to the isogenic wild-type triple MAPT-mutant human-induced pluripotent stem cells, bearing the pathogenic N279K, P301L, and E10+16 mutations, exhibit deficits in mitochondrial bioenergetics and present altered parameters linked to the metabolic regulation of mitochondria. Moreover, we demonstrate that the triple tau mutations disturb the cellular redox homeostasis and modify the mitochondrial network morphology and distribution. This study provides the first characterization of disease-associated tau-mediated mitochondrial impairments in an advanced human cellular tau pathology model at early disease stages, ranging from mitochondrial bioenergetics to dynamics. Consequently, comprehending better the influence of dysfunctional mitochondria on the development and differentiation of stem cells and their contribution to disease progression may thus assist in the potential prevention and treatment of tau-related neurodegeneration.
Keywords: Tubulinas; Estrés oxidativo; Mitocondrias; Tau protein; Induced pluripotent stem cells; Mitochondria; Bioenergetics; Oxidative stress; Dynamics